2018
DOI: 10.1007/978-1-4939-7493-1_11
|View full text |Cite
|
Sign up to set email alerts
|

Mechanically Coupled Reaction-Diffusion Model to Predict Glioma Growth: Methodological Details

Abstract: Biophysical models designed to predict the growth and response of tumors to treatment have the potential to become a valuable tool for clinicians in care of cancer patients. Specifically, individualized tumor forecasts could be used to predict response or resistance early in the course of treatment, thereby providing an opportunity for treatment selection or adaption. This chapter discusses an experimental and modeling framework in which noninvasive imaging data is used to initialize and parameterize a subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 37 publications
0
35
0
Order By: Relevance
“…For example, the diffusion coefficient of cancer cells (i.e., the parameter “ D ” in Eq. (8)) can be correlated with the local von Mises stress by solving an elasticity boundary problem between the tumor and host tissue [13, 53, 54]. Hormuth et al assumed that solid stress would primarily affect the motility of tumor cells rather than the proliferation of cells [13].…”
Section: Mathematical Modeling Of Proliferation and Therapy Across Scmentioning
confidence: 99%
“…For example, the diffusion coefficient of cancer cells (i.e., the parameter “ D ” in Eq. (8)) can be correlated with the local von Mises stress by solving an elasticity boundary problem between the tumor and host tissue [13, 53, 54]. Hormuth et al assumed that solid stress would primarily affect the motility of tumor cells rather than the proliferation of cells [13].…”
Section: Mathematical Modeling Of Proliferation and Therapy Across Scmentioning
confidence: 99%
“…where N T (x -, t) is the tumor cell fraction at three-dimensional position xand time t, θ T is the tumor cell carrying capacity (i.e., the maximum packing fraction that a voxel can functionally support), and k p,T is the tumor cell proliferation rate. D T (x -, t) changes spatially and temporally as a function of the local tissue stress 8,14,15 In vitro experiments have demonstrated that tumor expansion is restricted as local mechanical stresses increase 11 . Thus, it is natural to relate D T (x -, t) to stress as shown in Eq.…”
Section: Mechanically Coupled Reaction Diffusion Model Of Tumor Growth-mentioning
confidence: 99%
“…where G is the shear modulus, ν is the Poisson's Ratio, and λ is second coupling constant. Literature values are used to assign G and v for different tissue regions within the brain (described in detail in 15 ) as we assume that these tissue properties will not change dramatically from animal to animal (we return to this important point in the Discussions section). Eqs.…”
Section: Mechanically Coupled Reaction Diffusion Model Of Tumor Growth-mentioning
confidence: 99%
See 1 more Smart Citation
“…And the third one is the solution algorithm.Regarding the underlying model, like us, most researchers focus on parameter calibration of a handful of model parameters using single-species reaction-diffusion equations [7,22,24,28,33,39,51,58,59]. While more complex models describing processes like mass effect, angiogenesis and chemotaxis [23,26,48,54,60] exist, they have not been considered for calibration due to theoretical and computational challenges. However, several groups, including ours, are working to address these challenges.Regarding the inverse problem setup, in most studies the authors use scans from two or more time points and assume that the tumor concentration is fully observed.…”
mentioning
confidence: 99%